Textured Activism: Affect Theory and Transformational Politics in Transnational Queer Palestine-Solidarity Activism - Kouri-Towe, Natalie (Atlantis, 2015)
How do we conceptualize social and political transformation? What possibilities arise for our political imaginings when we examine the approaches and orientations of activist practice in the everyday? Using queer and affect theory, I examine dualistic thinking in social movement practices to propose a model for thinking about the ethics of solidarity in practice. I consider this model of solidarity though the texture of activism and by examining the everyday practices of solidarity in the queer Palestine movement.